The visual ventral network is disconnected in Lewy body dementia with visual hallucinations: Neuroimaging / differential diagnosis. (7th December 2020) - Mehraram, Ramtin; Taylor, John‐Paul; Murphy, Nicholas; Rodriguez, Luis Peraza; Cromarty, Ruth; Graziadio, Sara; O'Brien, John T; Killen, Alison; Colloby, Sean J; Kaiser, Marcus
Abstract: Background: Visual hallucinations (VH) are a common symptom in Lewy body dementias (LBD), which comprise dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD). Previous studies investigated functional brain network alteration associated with VH in different diseases. However, there is a lack of studies on VH in LBD, and a clear picture of the affected pathways is still missing. In this study, we used electroencephalography (EEG) to detect the weakened cortical connections and the functionally disconnected cortical regions in LBD with VH. Method: Resting state eyes closed EEG signals (128 channels) were recorded from 45 LBD participants: 18 without VH (eight DLB) and 27 with VH (13 DLB). EEG time series were filtered (bandpass: 8‐13 Hz), and cleaned from artefacts. Magnetic resonance imaging (MRI) recordings were individually obtained with magnetisation prepared rapid gradient echo (MPRAGE) sequence, and source estimation was performed with sLORETA technique (Destrieux atlas). Connectivity was measured with weighted phase lag index (WPLI), and assessed with Network Based Statistics (NBS), including the MMSE score as covariate. Node strengths of the subnetworks detected with NBS was computed. The visual hallucination score was collected through the NPI questionnaire. Result: The NBS revealed two subnetworks affected in VH, both comprising regions belonging to the visual ventral pathway (p<0.05, t>3.8). The first one (Figure 1) comprised connections between the right temporal lobe and the prefrontal cortex, which showed reduced strength. In the second one (Figure 2), contra‐lateral connectivity between occipital and right infra‐temporal lobe was significantly weakened. Conclusion: We propose a topography of the subnetworks affected in LBD with VH. The first and second subnetworks comprise regions involved respectively in the top‐down and bottom‐up visual perception streams. Our results resonate with the literature related to the pathology of LBD and VH. We found indeed that both affected subnetworks comprise the right inferior temporal lobe, which has been previously found to show a great burden of Lewy bodies in patients with VH. Our results support EEG as a suitable biomarker for assessing the severity of the pathology, and providing useful insights into the disease.